Tricuspid Valve-in-Valve Procedure with An Edwards S3 Valve in a 15-kg Child in Latin America - Albert Franz Guerrero Becerra; Jaime Ramon Cabrales Arevalo; Julian Senosiain; Alberto Enrique Garcia Torres; Jaime Camacho; Nestor Fernando Sandoval Reyes (Brazilian Journal of Cardiovascular Surgery, 2022)
ABSTRACT A 5-year-old child, weighing 15 kg, with three previous sternotomies, presented with right heart failure due to severe stenosis and regurgitation of the bioprosthetic tricuspid valve. A percutaneous tricuspid valve-in-valve procedure with an Edwards S3 valve was ofered for compassionate use, performed with no complications and with a significant clinical condition improvement.